anonymous
  • anonymous
I was trying to find the roots of the polynomial f(x) = 4x^3+3x^2-6x-1. By Rolle's theorem, If there exists 2 different values of x, say x(1) and x(2) that returns a same value of f(x), then at some point between x(1) and x(2), d/dx[f(x)] = 0. ---> (1) Hence, I differentiate f(x) to get, d/dx[f(x)] = 12x^2+6x-6 By (1) 12x^2+6x-6 = 0 Solving for x, i get 2 roots, x = -1 and 1/2. Now solve for f(x) = 4x^3+3x^2-6x-1 with x = 1 (by changing the sign) and surprisingly, f(1) = 0 !!, seems to be one of the root of f(x). Can someone help me to understand this ?
OCW Scholar - Single Variable Calculus
schrodinger
  • schrodinger
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
I will explain you how to find roots of the f(x). First root we will guess. It will be 1 or -1. It is deviders of the last member of the equation. f(-1)=4*(-1)^3+3*(-1)^2-6*(-1)-1=-4+3+6-1=4 f(1)=4*(1)^3+3*(1)^2-6*(1)-1=4+3-6-1=0 => x_(1)=1 - the root devide column the equation: (4x^3+3x^2-6x-1)/(x-1)=4x^2+7x+1 then we find the roots of 4x^2+7x+1, D=7^2-4*4*1=33 x_(2)=(-1+sqrt(33))/8 x_(3)=(-1-sqrt(33))/8
anonymous
  • anonymous
Thx for the post, but my question was not about the roots of the equation. If u closely observe this, f'(x) = 12x^2+6x-6 has roots one of the roots as -1. and strangely, one of the roots of the equation, f(x) = 4x^3+3x^2-6x-1 is 1 [f(1) = 0] By changing the sign of one of the root of d/dx[f(x)], i actually get one of the real root of f(x). This is cool, but I cant figure out all the cases, where such a relationship can exist !!! Or to put it the other way, why does f(x) has root of 1 and d/dx[f(x)] has root of -1. I some how cant accept that this is just a coincidence..
anonymous
  • anonymous
it is concurrence, look at graphics http://www.yotx.ru/default.aspx?clr0=000000&exp0=4x+%5E+3+%2B3+X+%5E+2-6x-1+&mix=-5&max=5&asx=on&u=mm&nx=X&miy=-10&may=5&asy=on&ny=Y&iw=600&ih=400&ict=png&aa=on, in x=-1 and x=0.5 f(x) have extremums, in x_(1)=1, x_(2)= (-1+SQRT(33))/8, x_ (3)=(1-SQRT(33))/8 f(x) have roots for example, take another function, g(x)=5x^3+7x^2+2x-1, look http://www.yotx.ru/default.aspx?clr0=000000&exp0=5x%5E3%2B7x%5E2%2B2x-1&mix=-5&max=5&asx=on&u=mm&nx=X&miy=-10&may=5&asy=on&ny=Y&iw=600&ih=400&ict=png&aa=on, roots and extremums - the another dotes

Looking for something else?

Not the answer you are looking for? Search for more explanations.